Complete determination of the material composition of municipal solid waste incineration bottom ash. (1st February 2020) - Huber, Florian; Blasenbauer, Dominik; Aschenbrenner, Philipp; Fellner, Johann
Highlights: A characterisation of bottom ash from three different MSWI plants was performed. Most of iron and copper are present in the fraction >50 mm. About 50% of aluminium and brass are captured within pieces of mineral material. Glass is mainly present in the size fraction 8–16 mm. Batteries, coins, gold and silver are mostly present in the size fraction 16–50 mm. Abstract: Bottom ash from waste incineration is heterogeneous and contains different materials. Previous studies on the material composition of bottom ash provide only limited information as to composition, because large pieces present in bottom ash were not investigated nor were all materials were separated and analysed. The objective of the present study is to provide the complete and detailed composition of bottom ash encompassing and extensive range of different materials. Altogether, nine bottom ash samples with a mass of 3000 kg each were sieved to eight size fractions, whereby small particles adhering to larger pieces were separated by water and added to the respective size fractions. In the sorting analysis of all size fractions, the materials enclosed in molten mineral material and materials present as composites (e.g. transformers and batteries) were considered. The material characterisation revealed that the size fraction > 50 mm contains most of the iron (up to 50% of the total iron) and copper (about 20% of the total copper), while batteries, coins, silver and gold are almost exclusively present between 16 and 50 mm. The fractions between 8 and 16 mm show the highest share of aluminium (up to 50% of the total aluminium) and glass (up to 60% of the total glass). While the metal content is underestimated, if large pieces of material are disregarded, the multi-step approach applied in this study enables a complete determination of materials in bottom ash, which is essential for optimising material recovery in bottom ash treatment.